2006
DOI: 10.1016/j.jpba.2005.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Liquid separation techniques coupled with mass spectrometry for chiral analysis of pharmaceuticals compounds and their metabolites in biological fluids

Abstract: Determination of the chiral composition of drugs is nowadays a key step in order to determine purity, activity, bioavailability, biodegradation, etc, of pharmaceuticals. In this manuscript, works published for the last 5 years on the analysis of chiral drugs by liquid separation techniques coupled with mass spectrometry are reviewed. Namely, chiral analysis of pharmaceuticals including e.g., antiinflammatories, antihypertensives, relaxants, etc, by liquid chromatography-mass spectrometry and capillary electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 64 publications
(38 reference statements)
0
39
0
2
Order By: Relevance
“…This hyphenation enables to obtain information on the solute's molecular weight and structure and may enhance the sensitivity of certain compounds depending on their characteristics (proton affinity, absorptivity, etc.). In the last 10 years, there were many significant developments in CE-MS instrumentation and applications that have made CE-MS a competitive tool [9,52].…”
Section: End-column Detection In Chiral Analysis By Cementioning
confidence: 99%
See 1 more Smart Citation
“…This hyphenation enables to obtain information on the solute's molecular weight and structure and may enhance the sensitivity of certain compounds depending on their characteristics (proton affinity, absorptivity, etc.). In the last 10 years, there were many significant developments in CE-MS instrumentation and applications that have made CE-MS a competitive tool [9,52].…”
Section: End-column Detection In Chiral Analysis By Cementioning
confidence: 99%
“…Some reviews have been published in the last years covering the chiral separation of drugs [8][9][10] or pollutants and their metabolites [11]. The aim of this review is to provide a general view of the different strategies that have been used in the last years in order to enhance the sensitivity of detection in chiral analysis by CE with application to the analysis of drugs or biological, environmental, or food samples.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the vast exploration in this subject, numerous reviews detailing fundamentals and applications can be found in the literature prior to 2005 [6][7][8][9][10][11] and over the past two years [12][13][14][15]. Reviews have also covered methods developed specifically for pharmaceutical compounds [16][17][18][19][20][21][22], biological compounds [23], chiral LC-MS/ CE-MS [24], pesticides [25], pollutants [26], and food additives [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some other published reviews were focused on discussing the different applications of a particular CE technique, including food analysis. This is the case for instance of CE coupled to mass spectrometry (MS) [15][16][17], electrochromatography [18], CE coupled to chemiluminiscence detection [19], microemulsion electrokinetic chromatography (MEEKC) [20], sample treatment prior to CE-MS [21].…”
Section: Introductionmentioning
confidence: 99%